Validation of the Model of Instagram Addiction in Pakistan: A Study of University Students - Malik, Qurat-ul-Ain; Arshad, Rubab (Annals of Human and Social Sciences, 2025)
The aim of the research was to investigate the levels and existence of Instagram addiction amongst university students in Pakistan. The research was based on the instrument developed by Achmad Sholeh and Ahmad Rusdi called that The Instagram Addiction Scale (TIAS). The study used a quantitative survey approach and a sample of 600 respondents was taken from amongst the male and female students of International Islamic university, Islamabad. Findings of the study revealed that there was a moderate positive correlation between the levels of addiction and Instagram usage. Deeper analysis showed a similar relationship between Instagram usage and each component of addiction including mood-modification, relapse, salience, conflict, tolerance and withdrawal. Findings of the study showed that TIAS is a reliable and valid tool for evaluating the levels of Instagram addiction. Furthermore, contrary to prior literature, gender was not found to be a moderating factor in the levels of Instagram addiction.